A Model of Alumni Gift-Giving Behavior. AIR 1989 Annual Forum Paper - Volkwein, J. Fredericks ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Drawing upon both the fund-raising and outcomes literature, a gift-giving model is described that explains the connection between a variety of alumni demographic characteristics, previous university experiences, and gift-giving interest and capacity. Donor behavior is viewed as a function of both capacity and motivation. However, the personality and values that produce motivation and the socioeconomic status and achievements that produce capacity also are the products of the backgrounds and prior experiences of alumni. Academic experiences and demographic characteristics are both considered to be primary influences on the subsequent socioeconomic attainments of college graduates and their willingness to give. Using an alumni population at a public university, factor analytic techniques are used to derive a number of measures, involving demographic background, academic and social integration, capacity to give, motivation to give, and gift-giving behavior, reflecting the concepts in the model. The alumni questionnaire is appended. Contains 20 references. (Author/KM)
ERIC Note: Paper presented at the Annual Forum of the Association for Institutional Research (29th, Baltimore, MD, April 30-May 3, 1989).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alumni; Demography; Donors; Educational Experience; Fund Raising; Higher Education; Institutional Research; Motivation; Outcomes of Education; Questionnaires; Socioeconomic Status; AIR Forum; Reports, Research; Speeches/Meeting Papers; Tests/Questionnaires.